Results-oriented Strategic Management - Ministry of Planning case - Cavalcante, Paulo Henrique Fernandes (Seven Editora, 2023)
The objective of this research was to analyze the adherence of existing indicators and their sufficiency and, on this occasion, to evaluate the impacts. A strategic objective of IBGE was selected, among others, from the Strategic Planning of the Ministry of Planning for its analysis. The methodology of Strategic Management Oriented to Results (GEOR) was used and the progress, benefits and impacts were verified. It is concluded that there is effectiveness and efficiency of the indicators and that the citizen can identify the goods and services offered. DOI: https://doi.org/10.56238/methofocusinterv1-110